Determinants of improving productivity of dry-seeded rice in rainfed lowlands - Lantican, M.A.; Lampayan, R.M.; Bhuiyan, S.I.; Yadav, M.K. (Cambridge University Press, 1999)
Land and crop management practices were studied to determine yield stability and feasible measures to improve productivity of dry-seeded rice. Variability of yields among farms that had grown dry-seeded rice on the entire farm every season during the period 1991–95 was lower than among farms that had consistently grown transplanted rice during the same period. Weed control is a major challenge for dry-seeded rice and almost all farmers used herbicides to control weeds. Farmers who grew a non-rice crop before the rice season had better weed control than those who did not. Ploughing intensity and the type of implement used for land preparation were not significant factors for weed control. Field bund management was one determinant of productivity differences among farmers. The use of cross-bunds or periphery- and cross-bunds improved the efficiency of rainwater conservation and input use, and increased yields. Fields with higher levelling precision had lower water stress and produced better yields. On average, a farmer lost 0.93 t ha−1 yield due to land-levelling deficiency. The division of large and medium farms into a number of smaller plots improved levelling precision and water control, resulting in higher yields.